Comparative Microbiomes of the Respiratory Tract and Joints of Feedlot Cattle Mortalities - Chunli Li; Rahat Zaheer; Andrea Kinnear; Murray Jelinski; Tim A. McAllister (Microorganisms, 2022)
A comparative study of microbiota of the respiratory tract and joints of bovine respiratory disease (BRD) cattle mortalities was undertaken. Nasopharynx, trachea, lung and joint samples were collected from 32 cattle that died of BRD, “cases”, and 8 that died of other causes, “controls”. Bacterial diversity was lower (p < 0.05) in the nasopharynx, trachea and lungs of cases as compared to controls. In cases, alpha-diversity (p < 0.05) was lower in the lungs and joints than the nasopharynx. Proteobacteria, Tenericutes, Bacteroidetes, Firmicutes and Actinobacteria were the most abundant phyla in all samples. Relative abundances of Mycoplasma spp. in the lung, Pasteurella spp. in the trachea and lung, and Histophilus spp. in the lung, trachea and nasopharynx of cases were higher (p < 0.001) than controls. Mycoplasma spp. comprised 20.5% of bacterial flora in the joint, 36.0% in the lung, 22.4% in the trachea and 8.8% in the nasopharynx. Mannheimia spp. (21.8%) and Histophilus spp. (10.4%) were more abundant in lungs. Cattle that died of BRD possessed less diverse respiratory microbiomes with a higher abundance of respiratory pathogens. Mycoplasma spp. were prominent members of pneumonic lungs and joints displaying septic arthritis.